Substance use in childhood and adolescence and its associations with quality of life and behavioral strengths and difficulties - Wiebke Frobel; Nico Grafe; Christof Meigen; Mandy Vogel; Andreas Hiemisch; Wieland Kiess; Tanja Poulain (BMC, 2022)
Abstract Background Substance use in childhood and adolescence continues to be a current health concern. The aims of the present study were to identify trends in the use of alcohol, cigarettes, and cannabis in children and adolescents in the last 10 years and to assess associations between substance use and quality of life and behavioral strengths and difficulties. Methods Substance use was examined in 1829 9- to 18-year-old German children and adolescents participating in the LIFE Child cohort study between 2011 and 2020. Quality of life was investigated using the KIDSCREEN-27 questionnaire. The Strength and Difficulties Questionnaire was used to assess behavioral strengths and difficulties. Associations were assessed using linear regression analyses. All effects were adjusted for age, gender, and family socio-economic status. Results 38.44% of participants reported drinking alcohol at least sometimes. Smoking (6.23%) and the use of cannabis (3.94%) were less frequent. While we observed no significant changes in smoking between 2011 and 2021, the consumption of cannabis and the frequent consumption of alcohol has increased in this time period. Cigarette and cannabis use were associated with additional symptoms of hyperactivity/inattention and reduced prosocial behavior. For all three substances, usage was associated with more conduct problems. We also found significant associations between substance use and a lower quality of life in the areas of physical wellbeing, psychological wellbeing, parent relation and autonomy, and school environment. One noteworthy finding was that cigarette consumption and frequent alcohol use were associated with higher quality of life in terms of social support/peer group relations. Some significant interactions between substance use and child age indicated that associations between substance use and quality of life or behavioral difficulties were stronger in younger than in older children. Conclusions The results show that quality of life and behavioral difficulties are associated with substance use and should be considered when developing or implementing preventive measures to counter substance use. Furthermore, the findings indicate that substance use can be accompanied by improved peer relations. Therefore, the influence of peers, especially of peers who use these substances, should not be underestimated.